2015
DOI: 10.5897/ajmr2015.7526
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation and nutritional studies of an edible mushroom from North Brazil

Abstract: The vertical mycelial growth to investigate the feasibility of Pleurotus ostreatoroseus DPUA 1720 production in lignocellulosic Amazonic residues was evaluated. Mycelial development was carried out in cupuaçu exocarp (Theobroma grandiflorum Willd Former Spreng Schum), açai seed (Euterpe oleracea) and sawdust as substrates. Each residue was supplemented with rice bran, crown and pineapple peel. The average speed of mycelial growth was determined using three replicates for 15 days at 25°C in the absence and pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…These results are confirmed by Victor and Olatomiwa [30] who obtain moisture content of dried Pleurotus ostreatus ranges from 9.00% to 10.72%. The moisture content of Pleurotus ostreatus harvested from hardwood sawdust (Anogeissus leiocarpus) [32] was higher (8.93% db) than that harvested from softwood sawdust (Daniellia oliveri) (7.88% db) Ogundele, et al [31]. On cottonseed waste the moisture content was 8.45%, which is in the range of report of Manzi, et al [8] for the fruiting bodies of fresh P.ostreatus cultivated on different lignocellulosic agro-wastes.…”
Section: Moisture Contentmentioning
confidence: 72%
See 3 more Smart Citations
“…These results are confirmed by Victor and Olatomiwa [30] who obtain moisture content of dried Pleurotus ostreatus ranges from 9.00% to 10.72%. The moisture content of Pleurotus ostreatus harvested from hardwood sawdust (Anogeissus leiocarpus) [32] was higher (8.93% db) than that harvested from softwood sawdust (Daniellia oliveri) (7.88% db) Ogundele, et al [31]. On cottonseed waste the moisture content was 8.45%, which is in the range of report of Manzi, et al [8] for the fruiting bodies of fresh P.ostreatus cultivated on different lignocellulosic agro-wastes.…”
Section: Moisture Contentmentioning
confidence: 72%
“…The crude fat content of mushroom from hardwood sawdust (Anogeissus leiocarpus) were lower 1.72 % db compare to mushroom harvested from softwood sawdust (Daniellia oliveri) (1.81%) [31]. With rice bran substrate, fat contents was 3.8% [32]. To conclude, Pleurotus cultivated on hardwood sawdust (Anogeissus leiocarpus)…”
Section: Fat Contentmentioning
confidence: 83%
See 2 more Smart Citations
“…The açaí seed is an oleaginous seed formed by a small solid endosperm attached to a tegument rich in sugars. Several authors have characterized the kernel as containing cellulose (40.29 to 53.2%), hemicellulose (1.26 to 14%), lignin (4 to 22%), lipids (0.61 to 3.56%), total fiber (29 to 63%), total ash (0.15 to 1.7%), variable moisture (10.15%), protein (5 to 7%) and fixed carbon (0.83%) (Rodríguez-zúñiga et al, 2008;Qiu et.al., 2012;Tamiris et al, 2015;Cordeiro et al, 2019;Serrão et al, 2021). However, recent studies have shown that unlike what was previously reported, the fruit is predominantly composed of the polysaccharide mannan -which when hydrolyzed we obtain mannose -and not cellulose.…”
Section: Fermentationmentioning
confidence: 99%